Product Development of Yogurt Drink with Lactiplantibacillus plantarum subsp. plantarum Dad-13 - Kinanti Cahyaningati; Rini Yanti; Tyas Utami; Dian Anggraini Suroto; Endang Sutriswati Rahayu (Universitas Sebelas Maret (UNS), 2024)
Yogurt drink is a liquid yogurt with low viscosity produced through fermentation using the lactic acid bacteria Streptococcus thermophilus and Lactobacillus bulgaricus. The addition of the probiotic Lactiplantibacillus plantarum subsp. plantarum Dad-13 can improve the balance of gut microbiota and have health effects. This study aimed to determine whether the probiotic Lactiplantibacillus plantarum subsp. plantarum Dad-13 can be used as a co-culture in manufacturing yogurt drinks using starter cultures of Streptococcus thermophilus and Lactobacillus bulgaricus. The fermentation temperatures 37°C, 39°C, and 42°C were selected to determine the optimum temperature. Lactiplantibacillus plantarum subsp. plantarum Dad-13 can grow and synergize with yogurt starter culture at 37°C with a total lactic acid bacteria up to 109 CFU/mL at the end of the fermentation and a probiotic cell up to 108 CFU/mL. Cell viability, pH, total titratable acidity, viscosity, and color were also evaluated during 5 weeks of storage at 4°C. Until the end of storage, the total number of lactic acid bacteria had a value of 108 CFU/mL, and the number of probiotic cells had a value of 107 log CFU/mL. pH decreased, total titratable acid increased, viscosity changed, and the addition of probiotic did not affect the color during storage. As a result of sensory evaluation, the yogurt drink contained probiotic Lactiplantibacillus plantarum subsp. plantarum Dad-13 can still produce yogurt drinks similar to yogurt drinks without probiotics. Thus, Lactiplantibacillus plantarum subsp. plantarum Dad-13 could be utilized as a co-culture in making probiotic yogurt drinks.